Nonperturbative Yukawa couplings from string instantons - Blumenhagen, Ralph; Weigand, Timo (Physical review letters, 2008)
Nonperturbative D-brane instantons can generate perturbatively absent though phenomenologically relevant couplings for type II orientifold compactifications with D-branes. We discuss the generation of the perturbatively vanishing SU(5) GUT Yukawa coupling of type ⟨10 10 5H⟩. Moreover, for a simple globally consistent intersecting D6-brane model, we discuss the generation of mass terms for matter fields. This can serve as a mechanism for decoupling exotic matter.